Transformations in Argentina's Capitalist Development since the Neoliberal Age : Limits and Possibilities of a Peripheral Development Strategy - Féliz, Mariano (World Review of Political Economy.)
Capitalism in Argentina underwent some important transformations between the neoliberal era (1975-2001) and the new, neodevelopmentalist one (2002-2015). These changes conformed a new mode of peripheral participation of Argentina?s economy that has novelties as well as strong continuities, where State form and modes of intervention change. We'll show how this project of development reproduces, in a new context, and within new structural and subjective/political conditions, the historical process of combined and uneven development in Argentina. We propose to analyze such transformation, and assess their limitations for creating a sustainable option for capitalist reproduction in Argentina. Our analysis will provide an alternative view of recent capitalist development in Argentina that combines the process of class formation, class struggle and political conflict, with the structural tendencies of changing global capitalism